The Ideal Life, Jesus, and Prosperity Theology - Wildsmith, Andrew G. (Africa Journal of Evangelical Theology, 2014)
The article examines the Bible’s description of the ideal life (both Israelite and Canaanite), and then compares it with ideal life in traditional Africa, modern Western ideals, and also with the Prosperity Theology version of the ideal life. It then evaluates these in the light of Jesus’ experience of the elements of the ideal and successful life, and with the traditional Christian perceptions of heaven. It concludes with several implications for Africa today.
free